Hysterectomy with fetus insitu, in patient with uterine fibromatosis and premature preterm rupture of membrane: a case report - Seyedeh Houra Mousavi Vahed; Mahsa Dehghani; Seyedeh Azam Pourhoseini; Seyed Mostafa Pashang; Fereshteh Bazmi (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2020)
Introduction: Uterine myoma is a benign uterine mass that its prevalence in pregnancy is 1.6-10.7% and is associated with increased risk of obstetric complications and increased rate of cesarean and postpartum hemorrhage. Case presentation: The patient was a 34 years old woman, G4L2Ab1, with gestational age of 22 weeks who was hospitalized due to premature preterm rupture of membrane and uterine fibromatosis and large fibroid in cervix which blocked the birth channel. She was candidate for cesarean section and tubectomyand at the time of operation, after opening the abdomen, because possibility of massive hemorrhage, we decided hysterectomy with fetus insitu without incision on the uterus in order to prevention of massive hemorrhage and maternal morbidity (due to the complete parity and the patient's desire to remove the uterus). Conclusion: Hysterectomy with fetus insituis one of the methods in cases that uterus has multiple myoma and fetus is nonviable and parity is complete and there is indication for pregnancy termination by cesarean section. This method can be performed to prevent massive hemorrhage, transfusion and maternal morbidity.